The effect of application icon style design factors on the download intention of users - Manalac, Josea Ysabelle Tabuso (Animo Repository, 2021)
With the heavier reliance of the current generation to the digital world, mobile applications have become an integral part of smartphone users. The mobile application industry has been growing significantly and competition among applications and application developers have been fierce. All applications available in iOS App Store and Google Play Store are listed as icons. These icons serve as the initial visual representation of a mobile application and provide consumers a quick and intuitive representation of an application. It is the first and most powerful way to engage users in highly competitive app stores, thus, an effective mobile application icon design is essential for the success of an application to be downloaded. As icon style is identified as an element considered in the design of an icon, this study determines if the icon style design factors can help in the increased intention of users to download an application. By integrating a factor known to be affected by the use of an icon style, as well as affect the purchase (i.e. download) intention of users, this study was able to explore a reason for the effect of icon style design factors to download intention. This study also defined a set of icon style design guidelines that considered the significance of the icon style design factors. Emotion is the factor identified to have an effect on user download intention. It is also a factor that is determined by the use of icon style. Furthermore, emotion has been known to have an influence in the relationship of design and purchase/download intentions. With this thought, this study hypothesized emotion experienced by users to mediate the effect of the icon style design factors to their intention to download an application. Age has also been a common variable in icon style literatures wherein preferences, performances, etc. are said to be influenced by age of the user. Thus, this study hypothesized that age moderates the effect of the icon style design factors to the download intention of users. In order to prove the proposed hypotheses and suitably achieve the objectives of the study, the instrument of the main experiment was designed to simulate the scenario of browsing through an application store showing different redesigns of the same icon applying different levels of the icon style design factors. The respondents were surveyed regarding their chosen design, felt emotions, and download intention. After sufficient data was collected, it was analyzed using SEM analysis. From the results of the experimentation and analysis, the three icon style design factors considered were found to be significant in the download intention of users. Particularly, users are more inclined to download the icon design with subtle to no texture, subtle to no shadow, and bright or no highlights. Based on the post-interviews, the users would mainly base their response and selection from their perceived visual aesthetic of the icon. It was also determined from the analysis that emotion partially mediated the effect of the icon style design factors to download intention. With this, emotion can be used to explain the relationship between the icon style design factors to download intention. Based on the post-interview, the respondents said that the app icons with no texture and no shadow effects trigger their positive emotions more since they are more visually pleasing, thus, making them lean more to download the application with those icons. Lastly, no moderation effect was found from age. Increased exposure and familiarity of individuals of all ages in the digital world have led to potentially minimal difference in the effect of age in the relationship of the icon style design factors to emotion and download intention in this study.